Racism in the Twentieth Century in the Light of Church Teaching. Discussion of the Most Important Definitions and a New Interpretation of the Phenomenon - Piotr Walewski (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The paper undertakes the topic of racism and its moral evaluation by the Church's Magisterium. It begins with an inductive study which consists in a lexical analysis of selected texts of the Church's Magisterium and papal encyclicals aimed at tracing the topics of race and racism. The study has shown that although not numerous, the documents addressing this issue are very significant. The paper additionally reviews selected definitions of racism. Finally, the author makes an attempt to interpret the phenomenon of racism and provides a theological proposal to overcome this problem in a theoretical and definitional sense. The article is a contribution to further research and exploration.